Modified interpenetrating network structure gel powder as well as preparation method and application thereof
The modified interpenetrating network structure gel powder addresses the mechanical and tribological limitations of waterborne polyurethane coatings by enhancing the interaction between nanocellulose and nylon fibers, and incorporating inorganic nanoparticles to improve wear resistance and bonding strength.
Patent Information
- Application Number
- CN202411785902.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Waterborne polyurethane coatings suffer from poor mechanical properties, wear resistance, and limited industrial application due to issues such as bubble formation, low solid content, and weak intermolecular forces, which are exacerbated by the use of cellulose gels with poor dispersibility and high production costs.
A modified interpenetrating network structure gel powder is prepared by injecting a nylon mixed solution into a nanocellulose hydrogel solution, using aminosilane-modified inorganic nanoparticles to enhance mechanical properties and tribological performance, forming a network structure that improves adhesion and wear resistance.
The gel powder enhances the mechanical properties and wear resistance of polyurethane coatings by promoting interaction between nanocellulose and nylon fibers, with inorganic nanoparticles forming a reinforcing network that improves friction resistance and bonding strength.
Smart Images

Figure CN119241904A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of honeycomb materials, and in particular relates to a modified interpenetrating network structure gel powder and a preparation method and application thereof. Background Art
[0002] Polyurethane can be divided into two categories: solvent-based polyurethane and water-based polyurethane (WPU) due to its different dispersion medium. Water-based polyurethane is a polyurethane emulsion in which polyurethane resin uses water as the dispersion medium. In terms of structure, the rigid chain segment with ionic groups is hydrophilic, while the flexible chain segment plays a hydrophobic role; in terms of performance, it has the excellent characteristics of polyurethane resin. In terms of environmental impact, water-based polyurethane basically contains no or only trace amounts of organic compounds, and has the characteristics of being green, safe and non-toxic, low in manufacturing cost, and having many application fields. The demand for non-toxic, non-flammable and air-free resins has promoted the rapid development of water-based polyurethane.
[0003] The structure of waterborne polyurethane is a segmented polymer composed of soft segments and hard segments. Its performance is affected by its composition structure. The soft segments and hard segments form a unique separated microphase, which is the separated microphase that gives it many properties. Waterborne polyurethane has important application prospects in many industrial applications, such as coatings, adhesives, inks, glass fibers, paper pulp, synthetic leather, biomaterials, membranes and packaging films, and waterproof textiles.
[0004] The soft segment structure of waterborne polyurethane is composed of oligomer polyols, which have a great influence on its water resistance and mechanical strength. The hard segment structure is composed of isocyanate and small molecule chain extender, which has a great influence on the hardness, emulsion particle size and bonding performance of waterborne polyurethane after film formation. The structure of waterborne polyurethane can be adjusted in production. The soft segment provides flexibility and the hard segment provides rigidity. The main factors affecting its performance are the hydrogen bonds between hard-soft segments and hard-hard segments. With the increase of soft segment content, the degree of polymer crystallization and tensile properties are improved, but polyols are easily hydrolyzed, which will lead to poor water resistance. If you want to improve the hardness and bonding strength of waterborne polyurethane, you can increase the hard segment content appropriately, but if the hard segment content is too high, it will increase the chemical inertness of the chain segment, hinder the diffusion of the molecular chain, and lead to reduced bonding strength.
[0005] Waterborne polyurethane coatings not only require high gloss, color retention, scratch resistance and flame retardancy, but also protect materials from moisture, biological and chemical erosion. They are green, safe and pollution-free, and are often used in the fields of automobiles, construction, wood, paper, leather, and fabric coatings. However, waterborne polyurethane coatings use water as a carrier, and their lack of corrosion resistance is their biggest disadvantage, which to a certain extent affects their application in the industrial field. In addition, there are many problems in practical applications, such as a large number of bubbles generated during the reaction with water, which are difficult to eliminate and may remain in the coated film, affecting the various properties of the film. At the same time, due to their low solid content and weak intermolecular forces, the mechanical properties of waterborne polyurethane coatings are usually lower than those of traditional solvent-based polyurethane coatings, which has become a key bottleneck restricting their widespread application.
[0006] Blending modification is to physically blend the prepared WPU emulsion with other types of emulsions or some nanomaterials, and evenly disperse them through mechanical stirring or ultrasonic dispersion, so as to prepare the required functional coating. Nanomaterials refer to materials that have at least one dimension in the nanoscale range in three-dimensional space or are composed of them as basic units. Adding nanoparticles to polymers is one of the important methods to improve the performance of polymer materials. At present, there are many nanomaterials used to enhance and improve waterborne polyurethane, mainly including: nanocellulose, nanometal particles, nanocarbon materials, nanooxides, etc. CN118852963A discloses a heat-reflecting heat-insulating coating, in which nano-titanium dioxide is evenly dispersed in a cellulose aerogel matrix and a polyurethane coating, and the aggregation of nano-titanium dioxide is inhibited. The cellulose aerogel improves the flame retardant properties of the coating. CN117801653A discloses a highly elastic hydrophobic radiation-cured wood lacquer skin-feel coating, and the addition of hyperbranched nanocellulose hydrogel realizes the skin-tactile properties of the coating on the wood surface, and the physical and mechanical properties and durability of the coating are improved by reacting the -NH2 group in the hyperbranched nanocellulose hydrogel and the -NCO group in the radiation light-cured coating. CN110105531A and CN107474680A also disclose adding gel materials to the coating to improve the corresponding properties of the coating. However, the above-mentioned technology is only to add modified cellulose gel. As a natural fiber material, the mechanical properties of cellulose gel are relatively low; and cellulose gel has a large specific surface area. Due to the interaction between molecules and the influence of hydrogen bonds, cellulose gel is easily aggregated, so that its dispersibility and stability in polyurethane coatings are poor. At the same time, since the process of preparing cellulose gel is relatively complicated, the cost is high, and the yield is low, it is not suitable for large-scale industrialization.
[0007] On the other hand, WPU is an environmentally friendly binder material with the characteristics of easy modification and no pollution, and has great application prospects in the field of tribology. However, with the increasingly harsh working conditions of mechanical systems, the wear resistance and mechanical properties of pure WPU coatings are poor, and its durability and service life are limited. Pure WPU system coatings can no longer meet the required performance indicators. Therefore, many researchers have introduced micron or nano materials to prepare waterborne polyurethane-based composite coatings to meet the requirements of mechanical and tribological properties. Adding nanoparticles to polymers is one of the important methods to improve the performance of polymer materials. At present, there are many nanomaterials used to enhance and improve waterborne polyurethane, mainly including: nanocellulose, nanometal particles, nanocarbon materials, nanooxides, etc. WPU has made some progress in the research of tribology, but there are relatively few WPU coating material systems at present, and it is still necessary to further explore the improvement of the tribological properties of WPU coatings by other lubricating materials. Summary of the invention
[0008] The purpose of the present invention is to provide a modified interpenetrating network structure gel powder and its preparation method and application. The gel powder prepared by the method not only has an interpenetrating network structure, but also the introduction of nylon resin further improves the mechanical properties of cellulose gel, and the nylon resin itself contains more amide groups, which greatly improves the compatibility of nanocellulose and polyurethane coating; and the addition of inorganic nanoparticles further improves the mechanical properties of the gel material, and when used in polyurethane coating, improves the tribological properties of WPU coating.
[0009] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Using an aminosilane coupling agent to modify inorganic nanoparticles to prepare modified inorganic nanoparticles; (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; (3) dissolving nylon powder and polyvinyl pyrrolidone in an acidic solvent to obtain a nylon solution, then adding the modified inorganic nanoparticles into the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is (0.01-0.4):1; (4) Under stirring conditions, injecting the nylon mixed solution into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0010] Cellulose is a common high molecular polymer in nature, widely found in plants such as cotton, hemp and wood, and has the advantages of good biocompatibility, renewability, biodegradability, environmental friendliness and non-toxicity. Nanocellulose is made from cellulose, and has at least one dimensional space size of less than 100nm. Nanocellulose composite hydrogel materials not only retain the unique physical and chemical properties of cellulose, such as hydrophilicity, biocompatibility, biodegradability, high chemical activity and dimensional stability, but also have new structural characteristics given by micro-nano processing technology, such as light weight, softness, high specific surface area, high crystallinity, high strength, high modulus and mild chemical activity. Because the surface of cellulose nanofibers has abundant hydroxyl groups, cellulose exhibits high hydrophilicity, and can quickly form a uniform and stable nanocellulose suspension in the coating, which is widely used.
[0011] However, nanocellulose has low mechanical properties and has limited performance improvement on the coating. In addition, nanocellulose is prone to agglomeration due to its large specific surface area and strong hydrogen bonding, and has problems such as poor compatibility with the matrix and uneven dispersion. In the previous work (CN118895018A), the inventor first prepared graphene hydrogel and then directly added nylon / nanocellulose mixed solution. The fibrous filler in this method can only be dispersed outside the hydrogel and cannot penetrate into the gel to form an interpenetrating structure. The nylon therein only plays a role of adhesion and has limited reinforcing effect. Subsequently, the inventor prepared polyimide-nanocellulose modified interpenetrating network structure gel powder. However, polyimide has poor processability and solubility. In order to configure the polyimide solution, it is necessary to start from the monomer raw material, first prepare a polyamic acid solution, and complete imidization in the process of preparing the gel. The above method not only prolongs the process steps; more importantly, polyamic acid, as an intermediate of polyimide, is extremely unstable and cannot be stored for a long time, which greatly limits its industrial application. Nylon itself not only has excellent mechanical properties, but is also soluble in some organic solvents but insoluble in water; in particular, the nylon solution itself is relatively stable and can be stored for a long time at room temperature.
[0012] Based on the above problems, the present invention first prepares nanocellulose gel and then prepares nylon nanofibers through a precipitation process. The precipitation method is a common process for preparing polymer nanofibers in the prior art, but directly pouring the nylon solution into the precipitate will produce micron or even millimeter-sized fibers, and it is impossible to prepare nanometer-sized fiber structures.
[0013] The present invention injects the nylon mixed solution into the nanocellulose hydrogel solution under stirring. Among them, the nanocellulose not only plays a role in forming an interpenetrating network structure; more importantly, under the state of rapid stirring, the nanocellulose fibers in the solution can play a "sickle"-like splitting role, so that the nylon mixed solution is split into bundles with smaller diameters, thereby reducing the diameter of the nylon fibers. In order to further make the fiber diameter reach the nanometer level, and also to enable the nylon solution to form a stable bundle structure in the rapidly stirred nanocellulose hydrogel solution and promote the generation of the nanofiber structure, the present invention adds a certain amount of polyvinyl pyrrolidone. On the one hand, the polyvinyl pyrrolidone molecule contains a pyridine ring structure, which can form a hydrogen bond with the amide group on the nylon, provide an adsorption force, and enable the nylon organic solution "bundle" to be stably dispersed in the nanocellulose hydrogel solution; on the other hand, polyvinyl pyrrolidone also has a hydrophilic effect, and can hydrate with water molecules in the nanocellulose hydrogel solution. When the nylon mixed solution is injected into the nanocellulose hydrogel solution, the adsorption force and hydration force of polyvinyl pyrrolidone cause polyvinyl pyrrolidone to disperse on the outer surface of the nylon organic solution "tow". Since polyvinyl pyrrolidone itself has a high viscosity, it can promote the stability of the "tow" structure. Under the shear force provided by stirring and the "cutting" effect of nanocellulose, the "tow" can gradually become longer and thinner, thereby increasing the aspect ratio of the nylon fiber and promoting the formation of the nanofiber structure. The molecular weight of polyvinyl pyrrolidone is not particularly limited, and its specific number average molecular weight can be 8000-200000.
[0014] WPU is a green and environmentally friendly material with a wide range of application prospects, but it has the problem of poor mechanical properties and wear resistance, and is often modified by introducing other lubricating materials. The present invention adopts a method of gel powder filling and inorganic nanoparticle modification to improve the mechanical properties and tribological properties of the WPU coating. The porous gel powder with good compatibility is used as a carrier to load inorganic rigid nanoparticles. The porous gel carrier can fully infiltrate the polyurethane resin, improve the adhesion to the inorganic nanoparticles, and prevent the friction from falling off. On the basis of playing a reinforcing role, the inorganic nanoparticles further improve the mechanical properties of the gel powder and improve the hardness and friction resistance of the coating. In particular, the inorganic nanoparticles used in the present invention are particles modified by aminosilane coupling agents. When the inorganic nanoparticles are treated with aminosilane coupling agents, silane is first hydrolyzed into silanols, and then the silanol groups react with the hydroxyl groups on the surface of the inorganic nanoparticles to form a covalent bond connection. This chemical bonding reaction forms a firm bond between the inorganic nanoparticles and the coupling agent. On the other hand, the amino group at the other end of the aminosilane coupling agent is an active polar group, which can easily form hydrogen bonds with the amide group, residual terminal amino group and terminal carboxyl group on nylon, further improving the interfacial bonding force between the inorganic nanoparticles and nylon. Therefore, during the precipitation process of the nylon solution, the inorganic nanoparticles are precipitated on the fiber surface with nanofibers as carriers, which not only improves the dispersion performance of the inorganic nanoparticles, but also enhances the adhesion of the gel powder to the particles, preventing the particles from falling off due to friction. In this way, as the nylon is precipitated, an inorganic nanoparticle network structure with an interpenetrating network gel powder as the skeleton is gradually formed, and this network structure can effectively improve the wear resistance of the coating. When the coating surface is rubbed, the inorganic nanoparticles in the network structure will roll, thereby converting sliding friction into rolling friction, and slippage will also occur between the inorganic nanoparticles, which all improve the wear resistance of the coating. On the other hand, on the surface of the friction pair, the inorganic nanoparticles can act as a function similar to a "bearing". As the load increases, the local temperature of the friction surface is high, and a layer of inorganic nanoparticle film with toughness and flexural strength greatly exceeding that of ordinary films is formed on the surface. Due to their small particle size, inorganic nanoparticles diffuse and fuse with the matrix under the action of high temperature and high pressure in the friction contact area, further bonding the coating and the matrix tightly together, preventing both coating shedding and severe abrasive wear.
[0015] Nylon is soluble in acid, acetone and some alcohol organic solvents. The reason why the present invention selects acid as the solvent of nylon is that acidic solvents can promote the formation of nanocellulose gel structure. In the process of injecting nylon mixed solution, the violent stirring process will inevitably cause the destruction of nanocellulose gel structure, and the acidic solution injected subsequently can repair the damaged gel structure and promote the stability of gel structure. If organic solvents such as acetone are adopted, due to the addition of high viscosity nylon, the damaged gel cannot be restored and cannot play a splitting effect, which affects the formation of nylon nanofiber.
[0016] The precipitation method is a common method for preparing fibers. During the formation process of precipitated fibers, polymer droplets enter the shear-flowing precipitant. Under the action of shear force, the polymer droplets are stretched and elongated. At the same time, the organic solvent in the polymer droplets and the coagulant water in the precipitant undergo double diffusion, and the polymer fibers are gradually precipitated. The inventors also used the dripping method to prepare polyimide precipitated nanofibers in previous work. However, the dripping method is suitable for polymers with good fluidity (such as polyamic acid); for nylon polymers, their acidic solutions have high viscosity and poor fluidity, especially after adding inorganic nanoparticles, the fluidity of the nylon mixed solution is greatly reduced. When the nylon nanofiber is prepared by the drop method, the drop size is difficult to control, and the drop contacts the nanocellulose gel aqueous solution at the liquid surface in a spherical structure, and the contact area between the drop and the precipitate is small; more importantly, under the gravity of the inorganic nanoparticles, the splitting effect of the nanocellulose at the liquid surface is difficult to play, and the precipitation of nylon will occur during the contact between the nylon solution and the precipitate at the liquid surface, further causing the inorganic nanoparticles to fall off, and cannot be attached to the nanofiber to form an interpenetrating structure with the nanocellulose. In order to increase the contact area between the nylon solution and the precipitate, the present invention adopts an injection method to prepare the precipitated fiber. Under stirring conditions, a syringe with a nozzle is used to inject the nylon mixed solution into the nanocellulose hydrogel solution; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution. The nylon solution added by injection can make the solution contact with the precipitate in a fine filamentous structure. Compared with the droplets formed by the drop method, the contact area between the solution and the precipitate is greatly increased, and the precipitated nylon fiber has better dispersibility. Moreover, because the nozzle is inside the nanocellulose hydrogel solution, the splitting effect of the nanocellulose fibers is more fully exerted, splitting the high-viscosity nylon mixed solution into smaller diameter tows, further reducing the diameter of the nylon fibers. In addition, the injection process is more conducive to dispersing inorganic nanoparticles into the gel powder, preventing the particles from falling off the nylon fibers, and building a reinforced network in three-dimensional space, thereby improving the friction resistance of the polyurethane coating.
[0017] In general, under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the nylon mixed solution can form a small liquid flow in the stirred nanocellulose hydrogel solution, and gradually precipitate to form nylon nanofibers, thereby forming an interpenetrating network structure with nanocellulose. As the nylon precipitates, the inorganic nanoparticles gradually disperse to the fiber surface with nylon as the carrier, which is conducive to the construction of an enhanced network of inorganic nanoparticles in space; thus, only a small amount of inorganic nanoparticles needs to be added to greatly improve the mechanical properties and friction resistance of the gel material.
[0018] This composite functional gel material not only retains the original properties of the gel material, but also combines the high strength and thermal stability of nanocellulose and nylon fibers, as well as the friction resistance of inorganic nanoparticles with the solution properties of hydrogels, making up for the "soft and weak" defects of nanocellulose gel materials in mechanical structure, and laying the foundation for potential application development of gels.
[0019] Furthermore, the specific preparation process of the modified inorganic nanoparticles in step (1) is: dispersing the inorganic nanoparticles in a mixed solution formed by ethanol and water, then adding an aminosilane coupling agent, and reacting at 40-60° C. for 1-2 hours; after the reaction is completed, filtering, washing with ethanol, and drying to obtain the modified inorganic nanoparticles.
[0020] Furthermore, in step (1), the aminosilane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, 3-diethylenetriaminopropylmethyldimethoxysilane and 3-diethylenetriaminopropyltrimethoxysilane.
[0021] Furthermore, the inorganic nanoparticles in step (1) are at least one of metal nanoparticles, oxide nanoparticles, and carbon nanoparticles. Furthermore, the inorganic nanoparticles are at least one of copper, gold, silver, platinum, silicon dioxide, titanium dioxide, carbon black, and graphite. Furthermore, the average particle size of the inorganic nanoparticles is 20-200 nm.
[0022] Furthermore, in step (1), the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is (0.1-0.4):1.
[0023] Furthermore, in step (2), the natural cellulose raw material is at least one of cotton, bamboo powder, waste paper, flax, sisal, straw, and bagasse; the treatment method includes at least one of high-pressure homogenization, acid hydrolysis, enzymatic hydrolysis, and TEMPO oxidation; the nanocellulose has a diameter of 10-100 nm and a length of 5-20 μm. Furthermore, the nanocellulose of the present invention is prepared by TEMPO oxidation. The full name of TEMPO is 2,2,6,6-tetramethylpiperidinyl oxide, which is an organic nitrogen oxide with weak oxidizing properties. This method has a short reaction time, is non-toxic, and has a low cost, and the morphology and size of the prepared nanocellulose are relatively uniform.
[0024] Furthermore, in step (2), the acidic steam bath is at least one of a formic acid steam bath, an acetic acid steam bath, a hydrochloric acid steam bath, and a nitric acid steam bath; and the steam bath treatment time is 2-10 hours. The steam bath method is to place the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution.
[0025] Furthermore, in step (2), the nanocellulose content in the nanocellulose hydrogel solution is 0.5-2wt%; in step (3), the mass ratio of nanocellulose to nylon powder is (1-2):1; the nylon content in the nylon mixed solution is 1-5wt%; and the mass ratio of nylon powder to modified inorganic nanoparticles is 1:(0.1-1). The surface of the inorganic nanoparticles modified by the aminosilane coupling agent is rich in active functional groups such as amino groups, which can form strong hydrogen bonds with the amide groups in nylon, which not only improves the loading efficiency of the inorganic nanoparticles, but also improves their dispersion properties. Furthermore, the mass ratio of nylon powder to modified inorganic nanoparticles is 1:(0.2-0.5). An appropriate amount of inorganic nanoparticles can not only improve the mechanical properties of the gel powder, but also avoid the destruction of the gel structure caused by excessive inorganic fillers.
[0026] Furthermore, the acidic solvent used to dissolve nylon is at least one of a formic acid solution and a sulfuric acid solution.
[0027] Furthermore, in step (4), the nozzle has 1-4 nozzles; the nozzle aperture is 0.1-1mm; and the injection rate of the nylon mixed solution is 1-3mL / min. By injecting the nylon solution through the nozzles provided on the nozzle, the injection rate can be adjusted by the number of nozzles and the size of the nozzle aperture; compared with the dropwise addition method, the addition rate and morphology of the nylon solution are easier to control. There is no particular limitation on the number and aperture of the nozzles on the nozzle, and they can be adjusted according to the required injection rate. In particular, when multiple nozzles are used, the nozzles are evenly distributed on the nozzle, and the evenly distributed nozzles are more conducive to the uniform injection of the nylon solution into the nanocellulose gel solution, and the nanocellulose fibers can fully play a splitting role, so that the nylon mixed solution is split into smaller diameter bundles, thereby reducing the diameter of the nylon fibers. Furthermore, the number of nozzles is 1, and the nozzle aperture is 0.3mm. Furthermore, a 1mL or 2mL syringe commonly used on the market can be selected for injection. Furthermore, the injection rate is 1.2-2mL / min. By adjusting the injection rate, the nylon mixed solution can be fully dispersed into the nanocellulose hydrogel solution, and the splitting effect of nanocellulose can be fully exerted.
[0028] Furthermore, in step (3), the nylon is at least one of nylon 6, nylon 66, nylon 12, nylon 56, nylon 610, and nylon 1212.
[0029] Furthermore, in step (4), the stirring rate is 600-800 rpm. An appropriate stirring rate can prevent the nylon nanofiber aspect ratio from being reduced due to a too fast stirring rate, and can also prevent the defect of a thick diameter caused by a too slow stirring rate.
[0030] On the other hand, the present invention also provides an application of the modified interpenetrating network structure gel powder, and the modified interpenetrating network structure gel powder is used in the field of polyurethane coatings.
[0031] The polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; and 0.5-5 parts of gel powder with a modified interpenetrating network structure.
[0032] The modified interpenetrating network structure gel powder prepared by injection method can make the nanocellulose and nylon nanofibers fully interact with each other, and the gel structure is more regular and the porosity is higher. The higher porosity is conducive to the full infiltration of polyurethane, and improves the bonding force between the gel powder and the polyurethane coating, thereby further improving the mechanical properties and anti-corrosion ability of the coating. In addition, the large number of hydroxyl groups on the surface of the nanocellulose in the gel powder will produce hydrogen bonds with the amino-modified inorganic nanoparticles, nylon nanofibers and polyurethane matrix molecules, which enhances the interfacial interaction between the gel powder and the polyurethane matrix, gives full play to the properties of the gel powder, and improves the friction resistance of polyurethane. Nylon nanofibers have high mechanical properties, which solves the "soft and weak" defect of nanocellulose gel materials in mechanical structure. Nanocellulose and nylon nanofibers form an interpenetrating structure, which makes the two fully entangled, exerts a synergistic reinforcement effect, and improves the density and mechanical properties of the polyurethane coating.
[0033] Compared with the prior art, the present invention has the following beneficial effects: (1) The modified interpenetrating network structure gel powder prepared by the injection method can make the nanocellulose and nylon nanofibers fully interact with each other, making the gel structure more regular and having a higher porosity. The higher porosity is conducive to the full infiltration of polyurethane, improving the bonding force between the gel powder and the polyurethane coating, thereby further improving the mechanical properties and anti-corrosion ability of the coating.
[0034] (2) First, prepare nanocellulose hydrogel and construct nanocellulose-based gel material. Then, inject the nylon mixed solution into the nanocellulose hydrogel solution under stirring. Under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the nylon mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution and gradually precipitate to form nylon nanofibers, thereby forming an interpenetrating network structure with nanocellulose.
[0035] (3) During the precipitation process of the nylon solution, the inorganic nanoparticles are precipitated on the fiber surface with the nanofibers as the carrier, which not only improves the dispersion performance of the inorganic nanoparticles, but also enhances the adhesion of the gel powder to the particles, preventing the particles from falling off due to friction. In this way, as the nylon is precipitated, an inorganic nanoparticle network structure with the interpenetrating network gel powder as the skeleton is gradually formed. This network structure can effectively improve the wear resistance of the coating.
[0036] (4) Compared with synthetic fibers such as polyimide, nylon fibers have low costs and nylon solutions do not need to be prepared in advance and can be used as needed, which greatly reduces production costs and process steps, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1A simple injection device used in the present invention; Figure 2 This is a scanning electron microscope image of the gel powder prepared in Example 10; Figure 3 This is a scanning electron microscope image of the gel powder prepared in Comparative Example 1. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application. Unless otherwise specified, the preparation raw materials and process conditions in the following examples and comparative examples are consistent. Among them, the specific preparation process of nanocellulose in the following examples and comparative examples is as follows: (1) Removal of wax from bamboo powder: Add bamboo powder to a mixed solution composed of toluene and ethanol (volume ratio 3:1), mechanically stir for 24 hours, wash and dry, and set aside; (2) Removal of lignin from bamboo powder: Add the product of step (1) to a three-necked flask, then add 2wt% sodium chlorite solution, adjust the pH to 4, and react at 80°C for 6h, wash and dry, and set aside; (3) Removal of hemicellulose from bamboo powder: Add the product of step (2) to a 5wt% potassium hydroxide solution, stir at 90°C for 3h, wash and dry, and set aside; (4) Formation of nanocellulose: disperse bamboo cellulose powder in a mixed solution of TEMPO, sodium bromide and distilled water, slowly add sodium hypochlorite into the solution, stir evenly, adjust the pH to 10 and react for 4 hours, centrifuge and wash to obtain TEMPO-treated cellulose; the mass ratio of bamboo cellulose powder, TEMPO, sodium bromide and sodium hypochlorite is 1:0.02:0.1:2; place the TEMPO-treated cellulose in an ultrasonic cell crusher for 30 minutes, and freeze-dry to obtain nanocellulose with a diameter of 80 nm and a length of 10 μm.
[0039] Example 1 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Dispersing inorganic nanoparticles in a mixed solution of ethanol and water, then adding an aminosilane coupling agent, and reacting at 40°C for 2 hours; filtering after the reaction, washing with ethanol, and drying to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 4 h; the nanocellulose content in the nanocellulose hydrogel solution is 0.5 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt % formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles into the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.04:1; the mass ratio of nanocellulose to nylon powder is 1:1; the nylon content in the nylon mixed solution is 1 wt %; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.2; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.2 mL / min; the stirring rate is 600 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0040] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0041] Example 2 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Dispersing inorganic nanoparticles in a mixed solution of ethanol and water, then adding an aminosilane coupling agent, and reacting at 60°C for 1 hour; filtering after the reaction, washing with ethanol, and drying to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 8 h; the nanocellulose content in the nanocellulose hydrogel solution is 2 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles to the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.25:1; the mass ratio of nanocellulose to nylon powder is 2:1; the nylon content in the nylon mixed solution is 5 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.5; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 2 mL / min; the stirring rate is 800 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0042] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0043] Example 3 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Dispersing inorganic nanoparticles in a mixed solution of ethanol and water, then adding an aminosilane coupling agent, and reacting at 60°C for 2 hours; filtering after the reaction, washing with ethanol, and drying to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 8 h; the nanocellulose content in the nanocellulose hydrogel solution is 0.5 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles to the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.25:1; the mass ratio of nanocellulose to nylon powder is 1:1; the nylon content in the nylon mixed solution is 1 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.5; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.2 mL / min; the stirring rate is 800 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0044] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0045] Example 4 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added to react at 45°C for 1.8 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 5 h; the nanocellulose content in the nanocellulose hydrogel solution is 1 wt%; (3) Nylon powder and polyvinyl pyrrolidone were dissolved in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone was 30,000; then the modified inorganic nanoparticles were added to the nylon solution, and a nylon mixed solution was obtained after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder was 0.15:1; the mass ratio of nanocellulose to nylon powder was 1.2:1; the nylon content in the nylon mixed solution was 2 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles was 1:0.3; and the nylon was nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.4 mL / min; the stirring rate is 650 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0046] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0047] Example 5 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added and reacted at 55°C for 1.3 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 7 h; the nanocellulose content in the nanocellulose hydrogel solution is 1.6 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles into the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.8:1; the nylon content in the nylon mixed solution is 4 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.4; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the solution is exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the injection is performed using a 1 mL medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.8 mL / min; the stirring rate is 750 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0048] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0049] Example 6 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added to react at 50°C for 1.5 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 h; the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles into the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.4:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.3; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the hydrogel with an interpenetrating network structure is obtained by exchanging with deionized water solvent; the injection is performed using a 1 mL medical syringe, that is, the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.6 mL / min; the stirring rate is 700 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0050] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0051] Example 7 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added to react at 50°C for 1.5 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 h; the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles to the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.3; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the hydrogel with an interpenetrating network structure is obtained by exchanging with deionized water solvent; the injection is performed using a 1 mL medical syringe, that is, the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 3 mL / min; the stirring rate is 700 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0052] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0053] Example 8 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added to react at 50°C for 1.5 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 h; the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles into the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.1; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the hydrogel with an interpenetrating network structure is obtained by exchanging with deionized water solvent; the injection is performed using a 1 mL medical syringe, that is, the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.6 mL / min; the stirring rate is 700 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0054] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0055] Example 9 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added to react at 50°C for 1.5 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 h; the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles to the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:1; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the hydrogel with an interpenetrating network structure is obtained by exchanging with deionized water solvent; the injection is performed using a 1 mL medical syringe, that is, the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.6 mL / min; the stirring rate is 700 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0056] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0057] Example 10 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added to react at 50°C for 1.5 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 h; the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles to the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.3; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the hydrogel with an interpenetrating network structure is obtained by exchanging with deionized water solvent; the injection is performed using a 1 mL medical syringe, that is, the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.6 mL / min; the stirring rate is 700 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0058] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0059] Comparative Example 1 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added to react at 50°C for 1.5 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 h; the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%; (3) Dissolving nylon powder and polyvinyl pyrrolidone in a 88 wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of the polyvinyl pyrrolidone is 30,000; then adding the modified inorganic nanoparticles to the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3 wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.3; and the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution was added dropwise to the nanocellulose hydrogel solution; after the addition was completed, the solution was exchanged with deionized water solvent to obtain an interpenetrating network structure hydrogel; the nylon mixed solution dropwise acceleration rate was 1.6 mL / min; the stirring rate was 700 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0060] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0061] Comparative Example 2 A method for preparing a modified interpenetrating network structure gel powder comprises the following steps: (1) Inorganic nanoparticles are dispersed in a mixed solution of ethanol and water, and then an aminosilane coupling agent is added to react at 50°C for 1.5 hours; after the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain modified inorganic nanoparticles; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are silicon dioxide; the average particle size of the inorganic nanoparticles is 120 nm; the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is 0.3:1; (2) placing a deionized water dispersion of nanocellulose and polyvinyl pyrrolidone in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; the nanocellulose has a diameter of 80 nm and a length of 10 μm; the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 h; the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%; (3) Dissolving nylon powder in 88wt% formic acid aqueous solution to obtain a nylon solution, wherein the number average molecular weight of polyvinyl pyrrolidone is 30000; then adding the modified inorganic nanoparticles into the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; the mass ratio of polyvinyl pyrrolidone to nylon powder is 0.2:1; the mass ratio of nanocellulose to nylon powder is 1.5:1; the nylon content in the nylon mixed solution is 3wt%; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:0.3; the nylon is nylon 66; (4) Under stirring conditions, the nylon mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, the hydrogel with an interpenetrating network structure is obtained by exchanging with deionized water solvent; the injection is performed using a 1 mL medical syringe, that is, the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the nylon mixed solution injection rate is 1.6 mL / min; the stirring rate is 700 rpm; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
[0062] A polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion and 3 parts of modified interpenetrating network structure gel powder.
[0063] Performance test: The polyurethane coatings prepared in Examples 1-10 and Comparative Examples 1-2 were subjected to hardness test (GB / T6739-2006), paint film adhesion test (GB / T 5210-2006), salt spray resistance test (GB / T1771-2007) and abrasion resistance test (GB / T 1768-2006); the test results are shown in Table 1.
[0064] Figure 2-3 The following are the scanning electron microscope images of the gel powder prepared in Example 10 and Comparative Example 1. Figure 2 It can be seen that the precipitated nylon nanofibers and nanocellulose form an interpenetrating network structure, while the inorganic nanoparticles are evenly dispersed on the fiber surface. This indicates that under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the nylon mixed solution can form a fine liquid flow in the stirred nanocellulose hydrogel solution, and gradually precipitate to form nylon nanofibers, thereby forming an interpenetrating network structure with nanocellulose. As nylon precipitates, the inorganic nanoparticles gradually disperse to the fiber surface with nylon as the carrier, which is conducive to the construction of an enhanced network of inorganic nanoparticles in space; thus, only a small amount of inorganic nanoparticles needs to be added to greatly improve the mechanical properties and friction resistance of the gel material. Comparative Example 1 shows that when the droplet method is used to prepare nylon nanofibers, the droplet size is difficult to control, and the droplet contacts the nanocellulose gel aqueous solution at the liquid surface in a spherical structure, and the contact area between the droplet and the precipitate is small; more importantly, under the gravity of the inorganic nanoparticles, the nanocellulose at the liquid surface is difficult to split, and nylon will precipitate during the contact between the nylon solution and the precipitate surface, further causing the inorganic nanoparticles to fall off and unable to attach to the nanofibers to form an interpenetrating structure with the nanocellulose. Figure 3It can also be seen that nylon does not form a fibrous structure, but is attached to the nanocellulose surface in a lamellar shape, and the modified inorganic nanoparticles are scattered on the nylon lamella. The gel structure has a low porosity, which seriously affects the wetting efficiency of polyurethane. The inorganic nanoparticles are difficult to play lubrication and wear-resistant effects because they are wrapped by nylon. Comparative Example 2 shows that polyvinyl pyrrolidone needs to be added to the nylon solution in advance. If it is added to the nanocellulose aqueous dispersion in advance, due to the presence of abundant hydroxyl groups on the nanocellulose surface, it will form a stronger hydrogen bond with polyvinyl pyrrolidone, and it is impossible to attach to the nylon surface added subsequently, and the nylon solution "tow" cannot be stably dispersed in the nanocellulose hydrogel solution, affecting the formation of polymer nanofibers.
[0065] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. A method for preparing a modified interpenetrating network structure gel powder, characterized in that: The following steps are involved: (1) Using an aminosilane coupling agent to modify inorganic nanoparticles to prepare modified inorganic nanoparticles; (2) placing the deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; (3) dissolving nylon powder and polyvinyl pyrrolidone in an acidic solvent to obtain a nylon solution, then adding the modified inorganic nanoparticles into the nylon solution, and obtaining a nylon mixed solution after ultrasonic dispersion; The mass ratio of polyvinyl pyrrolidone to nylon powder is (0.01-0.4):1; (4) Under stirring conditions, injecting the nylon mixed solution into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; (5) The interpenetrating network structure hydrogel is freeze-dried and crushed to obtain a modified interpenetrating network structure gel powder.
2. The method for preparing a modified interpenetrating network structure gel powder according to claim 1, characterized in that: The specific preparation process of the modified inorganic nanoparticles in step (1) is as follows: dispersing the inorganic nanoparticles in a mixed solution formed by ethanol and water, then adding an aminosilane coupling agent, and reacting at 40-60° C. for 1-2 hours; filtering after the reaction, washing with ethanol, and drying to obtain the modified inorganic nanoparticles.
3. The method for preparing a modified interpenetrating network structure gel powder according to claim 1, characterized in that: In step (1), the aminosilane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltriethoxysilane, 3-diethylenetriaminopropylmethyldimethoxysilane and 3-diethylenetriaminopropyltrimethoxysilane.
4. The method for preparing a modified interpenetrating network structure gel powder according to claim 1, characterized in that: In step (1), the inorganic nanoparticles are at least one of metal nanoparticles, oxide nanoparticles, and carbon nanoparticles; and the average particle size of the inorganic nanoparticles is 20-200 nm.
5. The method for preparing a modified interpenetrating network structure gel powder according to claim 1, characterized in that: In step (1), the mass ratio of the aminosilane coupling agent to the inorganic nanoparticles is (0.1-0.4):
1.
6. The method for preparing a modified interpenetrating network structure gel powder according to claim 1, characterized in that: The diameter of the nanocellulose in step (2) is 10-100 nm and the length is 5-20 μm; the acidic vapor bath is at least one of a formic acid vapor bath, an acetic acid vapor bath, a hydrochloric acid vapor bath, and a nitric acid vapor bath; the vapor bath treatment time is 4-8 hours; the nanocellulose content in the nanocellulose hydrogel solution in step (2) is 0.5-2 wt%; the mass ratio of nanocellulose to nylon powder in step (3) is (1-2):1; the nylon content in the nylon mixed solution is 1-5 wt%; the acidic solvent is at least one of a formic acid solution and a sulfuric acid solution; the mass ratio of nylon powder to modified inorganic nanoparticles is 1:(0.1-1).
7. The method for preparing a modified interpenetrating network structure gel powder according to claim 1, characterized in that: In step (4), the nozzle has 1-4 nozzles; the nozzle aperture is 0.1-1 mm; the nylon mixed solution injection rate is 1-3 mL / min; the nylon in step (3) is at least one of nylon 6, nylon 66, nylon 12, nylon 56, nylon 610, and nylon 1212; and the stirring rate in step (4) is 600-800 rpm.
8. A modified interpenetrating network structure gel powder, characterized in that: The modified interpenetrating network structure gel powder is prepared by the preparation method of any one of claims 1 to 7.
9. An application of a modified interpenetrating network structure gel powder as claimed in claim 8, characterized in that: The modified interpenetrating network structure gel powder is used in the field of polyurethane coatings.
10. A polyurethane coating, characterized in that: The invention comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; and 0.5-5 parts of the modified interpenetrating network structure gel powder according to claim 8.
Citation Information
Patent Citations
Temperature-controlling heat-insulating temperature-reducing intelligent outdoor fabric based on microcapsules and aero-gels
CN106521974A
Nylon carbon nanotube graphene aerogel as well as preparation method and application thereof
CN118812911A
Gel powder with high mechanical property as well as preparation method and application of gel powder
CN118895018A
An auxetic structure, a support structure, a method of preparing an auxetic structure, and use of a cellulosic material
US20230218379A1
